Penggunaan Indikator Film Edible berbasis Antosianin Hibiscus rosa-sinensis L untuk Monitoring Kesegaran Tomat Ceri - Dewi Enggar Fitriani; Bambang Kuswandi; Lestyo Wulandari (Pustaka Kesehatan, 2022)
Fruit and vegetable are food products that are in great demand by the public. One of the fruit and vegetable products that can be enjoyed by the community is cherry tomatoes. Therefore, they required for quality of cherry tomato products, in this regard, the method was needed to determine the freshness of cherry tomatoes easily and practically. The purpose of this study was to develop an edible freshness sensor based on anthocyanin of shoe flower extract (Hibiscus rosa-sinensis L) with edible membrane from a mixture of chitosan and rice starch. The edible freshness sensor can be applied as a freshness sensor and determine the freshness level of cherry tomatoes with various parameters. The freshness evaluation of cherry tomatoes included weight loss test, pH, texture, and organoleptic test. The color change of the edible freshness sensor can be detected by the nude eye and analyzed by using ImageJ program to determine the value of the mean red of RGB. The results showed the color change of the freshness sensor which was dark grey when the cherry tomatoes were fresh, dark purple when the cherry tomatoes were still fresh and reddish-purple when cherry tomatoes were no longer fresh. The value of mean red from the edible freshness sensor increase with decreasing the freshness level of cherry tomatoes